A Qualitative Study on the Motivation to Go to Work by Workers in Crisis Areas Like the Southwest Region of Cameroon - Alandang, Marius Azenkeng; Manga, Menyomo Alain Marcel (Archives of Business Research, 2022)
This research is motivated by the desire to understand what motivates people to go to work despite the prevalence of the ongoing socio-political upheavals plaguing some regions of Cameroon and the southwest region in particular. The achievement of this main objective led us, through the interpretavist research design, to adopt the qualitative method. Through the interpretavist research design and based on the qualitative research method We did carry out our empirical data using a semi-structured interview guide administered to 16 teachers working in the said region through the purposive random sampling method and based on proximity. Our data was analysed using the manual data treatment method. The results of our analysis indicated that, there are various reasons that motivate workers to go to work. Prominent among the reasons is the learners’ future, self-satisfaction (intrinsic motivation) as well as administrative constraints (extrinsic motivation).